2008
DOI: 10.1002/ffj.1886
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivar and cultivation on sensory profiles of fresh strawberries and their purées

Abstract: The purpose of this study was to delineate and compare the sensory profiles of four different strawberry cultivars (Fragaria × ananassa Duch.), Elsanta, Marmolada, Maya and Queen Elisa, grown in Croatia in both conventional and organic cultivation. Sensory profiles of the fresh fruit and their purées were determined by quantitative descriptive analysis (QDA). ANOVA was applied to establish the differences between the intensities of sensory attributes of the fresh strawberries and their purées, arising from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Vermeir et al (2009) found a lower correlation (R 2 = 0.62) between the SS and the total concentration of sugars, indicating that other components such as acids also contribute to the SS. Kovacevic et al (2008) has confirmed that sweetness was positively correlated with the amount of soluble solids, but also with total soluble sugars and fructose. Perkins-Veazie (1995) reported that the sugar:acid ratio is possibly more important for the perception of sweetness for the sensory panel than soluble solids alone.…”
Section: Discussionmentioning
confidence: 67%
“…Vermeir et al (2009) found a lower correlation (R 2 = 0.62) between the SS and the total concentration of sugars, indicating that other components such as acids also contribute to the SS. Kovacevic et al (2008) has confirmed that sweetness was positively correlated with the amount of soluble solids, but also with total soluble sugars and fructose. Perkins-Veazie (1995) reported that the sugar:acid ratio is possibly more important for the perception of sweetness for the sensory panel than soluble solids alone.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the panel was unable to differentiate strawberries through the application of citrus aroma and earthy flavor attributes. 1‐Octen‐3‐ol has been documented as contributing to earthy aroma in strawberry fruit (Kovačević, Vahčić, Levaj, & Dragović‐Uzelac, ), and linalool contributing to the citrus aroma (Du, Plotto, Baldwin, & Rouseff, ). Means and variances for these 2 attributes were both low.…”
Section: Resultsmentioning
confidence: 99%